Corporate Social Responsibility and International Human Rights Law - McCorquodale, Robert (Journal of business ethics, 2009)
The United Nations Special Representative on Transnational Corporations and Human Rights, John Ruggie, has adopted a new framework for considering this issue within the international legal system. This article examines this framework in terms of its coherence, its consistency with international human rights law and how it can be ‘operationalized’ (which is required by the United Nations). In regard to the states legal obligation to protect human rights, it is considered whether this obligation is broader and deeper than is envisaged in the framework, especially if it can include the extra-territorial activities of corporations. The corporate responsibility to respect human rights is examined in terms of its conceptual and definitional problems, and the article also questions whether there will be sufficient legal remedies available to victims under the framework.